2023
DOI: 10.1002/acr2.11537
|View full text |Cite
|
Sign up to set email alerts
|

Guselkumab, a Selective Interleukin‐23 p19 Subunit Inhibitor, Resolves Dactylitis in Patients With Active Psoriatic Arthritis: Pooled Results Through Week 52 From Two Phase 3 Studies

Abstract: Objective Previous analyses of pooled DISCOVER‐1 and DISCOVER‐2 data through Week 24 showed significantly higher rates of dactylitis resolution in patients treated with guselkumab compared with placebo. Here, we investigate associations between dactylitis resolution and other outcomes through 1 year. Methods Patients were randomized 1:1:1 to receive subcutaneous injections of guselkumab 100 mg at Week 0, Week 4, and then every 4 or 8 weeks, or placebo with crossover to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
2
3
0
Order By: Relevance
“…Specifically, a greater proportion of guselkumab-randomized patients achieved such improvements compared with placebo at week 24 and demonstrated a clinically meaningful improvement in fatigue at week 52 across studies. We found that DR was associated with an increased likelihood of achieving fatigue response among biologic-naïve patients enrolled in DISCOVER-2, which is consistent with the findings from analyses previously conducted in the larger population of both biologic-naïve and -experienced patients with dactylitis in the pooled DISCOVER-1 and -2 population [ 22 ]. In that report, mediation analyses demonstrated the substantial direct effect of guselkumab on fatigue beyond its impact on achievement of MDA or 20% improvement in ACR response criteria or on changes in CRP levels.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Specifically, a greater proportion of guselkumab-randomized patients achieved such improvements compared with placebo at week 24 and demonstrated a clinically meaningful improvement in fatigue at week 52 across studies. We found that DR was associated with an increased likelihood of achieving fatigue response among biologic-naïve patients enrolled in DISCOVER-2, which is consistent with the findings from analyses previously conducted in the larger population of both biologic-naïve and -experienced patients with dactylitis in the pooled DISCOVER-1 and -2 population [ 22 ]. In that report, mediation analyses demonstrated the substantial direct effect of guselkumab on fatigue beyond its impact on achievement of MDA or 20% improvement in ACR response criteria or on changes in CRP levels.…”
Section: Discussionsupporting
confidence: 89%
“…Through the last efficacy assessment (week 100), two-thirds of guselkumab-treated patients achieved ER and three-quarters achieved DR. These results are similar to those based on pooled analyses through 1 year in subpopulations with enthesitis and/or dactylitis in both DISCOVER studies as well as the phase 2 study of guselkumab in PsA, which included patients with and without prior biologic experience [ 22 , 23 , 40 ]. The robust efficacy of guselkumab reported here further highlights the central role of the IL-23/IL-17 immune axis in the pathogenesis of PsA.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In the phase 3 PSUMMIT-1 and PSUMMIT-2 studies of the IL-12/23 inhibitor ustekinumab, significantly greater improvements in enthesitis and dactylitis were observed in ustekinumab-treated patients compared with those patients who received placebo [ 22 , 23 ]. In the phase 3 DISCOVER-1 and DISCOVER-2 studies, the IL-23 inhibitor guselkumab demonstrated higher rates of enthesitis and dactylitis resolution compared with placebo [ 24 , 25 ]. These results indicate that IL-23 inhibition is efficacious in improving and resolving enthesitis and/or dactylitis in patients with PsA.…”
Section: Discussionmentioning
confidence: 99%